2014
DOI: 10.1002/jcb.24761
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Sulfoxide Attenuates Hydrogen Peroxide‐Induced Injury in Cardiomyocytes via Heme Oxygenase‐1

Abstract: The antioxidant property of dimethyl sulfoxide (DMSO) was formerly attributed to its direct effects. Our former study showed that DMSO is able to induce heme oxygenase-1 (HO-1) expression in endothelial cells, which is a potent antioxidant enzyme. In this study, we hypothesized that the antioxidant effects of DMSO in cardiomyocytes are mediated or partially mediated by increased HO-1 expression. Therefore, we investigated whether DMSO exerts protective effects against H2 O2 -induced oxidative damage in cardiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
9
1
Order By: Relevance
“…The most plausible reasons for these discrepant results may be related to differences in species, cells and organs studied, concentration of OM used, and the nature and duration of the experimental injury. Consistent with other studies (Kruger et al , 2006; Man et al , 2014), H 2 O 2 independently increased HO-1 expression (Fig. 6), indicating that OM might activate Nrf2 via H 2 O 2 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most plausible reasons for these discrepant results may be related to differences in species, cells and organs studied, concentration of OM used, and the nature and duration of the experimental injury. Consistent with other studies (Kruger et al , 2006; Man et al , 2014), H 2 O 2 independently increased HO-1 expression (Fig. 6), indicating that OM might activate Nrf2 via H 2 O 2 .…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, investigators have shown that DMSO induces HO-1 expression via Nrf2 activation (Liang et al , 2011; Man et al , 2014); however, the concentration at which DMSO exerts these effects are significantly higher than that used in our study. So, it is highly unlikely that DMSO independently increased HO-1 expression in our study.…”
Section: Discussioncontrasting
confidence: 57%
“…DMSO exerts anti‐inflammatory effects as a hydroxyl radical scavenger (Man et al. ). DMSO also decreases IL‐1 β mRNA transcription and reduces inflammation (Ahn et al.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of maintaining dysfunctional mitochondria is a bioenergetics catastrophe, culminating in the disruption of the plasma membrane, resulting in necrosis [60, 61], which may explain the divergent apoptosis and necrosis results MMI-0100 affords cardiomyocytes in the present study. The unexpected early LDH release and necrosis occurring before caspase-3/7 activation may have to do with the use of DMSO as vehicle, which has been reported to attenuate oxidative stress induced apoptosis via inhibiting p38 to exert a cardioprotective effects via regulation of heme oxygenase-1 [62, 63]. …”
Section: Discussionmentioning
confidence: 99%